Natural killer cells in liver transplantation: Can we harness the power of the immune checkpoint to promote tolerance?. Issue 5 (15th December 2021) - Halma, Jennifer; Pierce, Stephen; McLennan, Rebecca; Bradley, Todd; Fischer, Ryan
Abstract: The roles that natural killer (NK) cells play in liver disease and transplantation remain ill‐defined. Reports on the matter are often contradictory, and the mechanisms elucidated are complex and dependent on the context of the model tested. Moreover, NK cell attributes, such as receptor protein expression and function differ among species, make study of primate or rodent transplant models challenging. Recent insights into NK function and NK‐mediated therapy in the context of cancer therapy may prove applicable to transplantation. Of specific interest are immune checkpoint molecules and the mechanisms by which they modulate NK cells in the tumor micro‐environment. In this review, we summarize NK cell populations in the peripheral blood and liver, and we explore the data regarding the expression and function of immune checkpoint molecules on NK cells. We also hypothesize about the roles they could play in liver transplantation and discuss how they might be harnessed therapeutically in transplant sciences.